2018
DOI: 10.1001/jamanetworkopen.2018.2777
|View full text |Cite
|
Sign up to set email alerts
|

Association of the Hospital Readmissions Reduction Program With Mortality During and After Hospitalization for Acute Myocardial Infarction, Heart Failure, and Pneumonia

Abstract: Key Points Question Was the announcement or implementation of the Hospital Readmissions Reduction Program (HRRP) associated with an increase in mortality following hospitalization for acute myocardial infarction, heart failure, or pneumonia among Medicare beneficiaries? Findings In this cohort study, between 2006 and 2014, in-hospital mortality decreased for the 3 conditions while 30-day postdischarge mortality decreased for acute myocardial infarction but … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
91
3
1

Year Published

2018
2018
2020
2020

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 108 publications
(98 citation statements)
references
References 33 publications
(92 reference statements)
3
91
3
1
Order By: Relevance
“…However, since the implementation of the HRRP, the inverse association between postdischarge mortality and readmission rates has reversed direction in some studies. Readmission rates have fallen but mortality rates, which some studies suggest had previously been decreasing, have been found by some studies to be stalled or increasing …”
Section: Discussionmentioning
confidence: 99%
See 4 more Smart Citations
“…However, since the implementation of the HRRP, the inverse association between postdischarge mortality and readmission rates has reversed direction in some studies. Readmission rates have fallen but mortality rates, which some studies suggest had previously been decreasing, have been found by some studies to be stalled or increasing …”
Section: Discussionmentioning
confidence: 99%
“…Using linked Get with the Guidelines‐Heart Failure Registry and Medicare data from 416 hospitals, Gupta and colleagues found that thirty‐day postdischarge risk‐adjusted readmission rates decreased from 20.0 percent to 18.4 percent after HRRP implementation, whereas 30‐day postdischarge risk‐adjusted mortality rate increased from 7.2 percent to 8.6 percent in the HRRP penalty phase, although these findings have been challenged by Khera et al Using CMS Hospital Compare data from 2009 to 2015, Chatterjee and Joynt Maddox found that between 2009 and 2015, heart failure, risk‐adjusted 30‐day mortality fell from 13.5 percent to 13 percent for 600 initially poor‐performing hospitals but increased from 10.9 percent to 12 percent (0.17 percent per year, P < .001) for the remaining 3196 hospitals. Wadhera et al found that thirty‐day postdischarge mortality for heart failure patients increased before HRRP announcement, but this trend accelerated significantly after HRRP announcement, driven largely by patients who were not readmitted (and perhaps who should have been).…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations